VITAMIN CONTENT OF MARINE RED ALGA CHAMPIA PARVULA - VINOTHKUMAR R; MURUGESAN S; SIVAMURUGAN V (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current investigation focuses on determining the vitamin content of marine red alga Champia parvula. Methods: Vitamins were divided and analyzed using Milichrom A-02 LC and multiwavelength ultraviolet visible as a detector. A 2 mm (ID)×250 mm (l) column was used to filter comprising C18 in the inverse stage used for separation. Results: The results suggest that the seaweed, C. parvula, contains 0.583±0.01, 3.43±0.01, 4.95±0.01, 1.95±0.01, 6.33±0.00, 174.74±0.01, and 15.75±0.01 μg of Vitamin A, B1, B5, folic acid, B12, C, and E, respectively, per gram of dry weight of the seaweed. Conclusion: The findings indicate that the seaweed, C. parvula, has a higher nutritional value and could be used as great dietary supplements for vitamins.